Natural Gas Consumption and Economic Growth in Top Gas-Producing African Countries - (:unkn) unknown (My University, 2023)
This study examined the impact of natural gas consumption on economic growth of some selected natural producing countries in Africa namely: Algeria, Angola, Egypt, Gabon, Libya and Nigeria over the period 1990 -2021 using Panel ARDL analysis. In order to achieve the purpose of the study data on growth rate of Gross domestic product (GDP), natural gas consumption, natural gas price and gasoline motor fuel consumption were sourced from the International Energy Agency and the World Bank. Gasoline motor fuel consumption was introduced as a check variable. The result shows that Natural gas consumption had a negative and insignificant impact on economic growth while Natural gas price and gasoline motor fuel consumption had positive and significant impact on economic growth. This implies that consumption of natural gas is not a significant determinant of economic growth among oil-producing countries in Africa. This may be attributed to the poor infrastructural development and lack of effective energy policies aimed at driving the transportation of liquified natural gas to households and manufacturing firms. In contrast, the price of natural gas and gasoline motor fuel contributed positively and significantly to the growth of the economies of oil-producing countries in Africa. This result may be due to revenue generated from export of liquified natural gas to Europe and some countries in Africa and the increase consumption of gasoline motor fuel in sub-Saharan Africa. As prices increases, revenue and foreign exchange also increases in the exporting countries. Based on these findings and conclusion, the study recommended: an improve infrastructure for natural gas utilization, stable and competitive price of natural gas and building of local capacity for refining of gasoline motor fuel as possible measures to achieving sustainable economic growth in gas producing countries in Africa.
Keywords: African Research